From Entertainment to Enlightenment : Media’s Role in the Lives of Borneo Muslim Converts - Salinayanti, Salim; Siti Aishah, Chu Abdullah (Universiti Kebangsaan Malaysia, 2025)
The rapid expansion of media platforms significantly transformed interactions with culture and religion. Drawing on mediatization theory, this study aims to investigate a contemporary issue, which is related to religious identity in the context of media consumption and entertainment. The participants of this study are Borneo Muslim converts in Sabah, Sarawak and Brunei. The study employed qualitative methods through semi-structured interviews with 15 Muslim converts. The data were categorized into themes and analyzed via Interpretative Phenomenological Analysis (IPA). The primary finding shows that Muslim converts in Borneo utilised media selectively, both as a resource for religious consumption and as a mechanism to strengthen their spirituality. These findings suggest the importance of media as a conduit for religious consumption and spiritual reinforcement through entertainment. It indicates that media producers and religious educators should consider the specific needs of this demographic to support their faith journey.